Menelaah Perkembangan Teori Sastra Indonesia - Aldi Firdaus; Fajar Subagja (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Literary studies are included in several normative fields, namely literary theory, literary history, literary criticism, comparative literature and also literary studies. Literature is seen by people to learn about literature. Literary history seeks to study and compile literary works as part of the intellectual historical process. In one society. Literary history can be seen as part of philosophy, because literary history itself is the same as the history of human thought towards objects of art or literary art that emphasizes on the more practical nature of the elaboration of the concept. Literary theory itself can be equated with aesthetic science with the beauty of science and also theory is certainly a different thing, with such assumptions, written literary theory is the same as writing history and aesthetics, including the field of literary art, theory needs to be studied so that there is no mistake in thinking about these two things. Literary theory itself has various meanings over time with the paradigm that is brought with it, literary theory can be interpreted as several ideas and methods used for the practice of reading literature. Literary theory is also interpreted as a way or step to understand literature. Views in literary theory also undergo changes along with the development of the human mindset itself.